Information Spillovers from Protests against Corporations: A Tale of Walmart and Target. (December 2013) - Yue, Lori Qingyuan; Rao, Hayagreeva; Ingram, Paul
In this study of the impact of protests against Walmart (a first entrant) on Target (a second entrant) from 1998 to 2008 in U.S. geographic markets, we develop and test a theory of information spillovers from protests against corporations proposing to enter a new market. We argue that the number of protests directed against a first entrant is a noisy signal for the second entrant because such protests are likely to be dominated by protest-prone activists and so do not reflect the sentiments of the community. The second entrant is likely to discount protests against the first entrant that are led by protest-prone activists and rely instead on protests led by local, decentralized activists as indicative of a community's preferences. We argue that the second entrant differentiates between protests against the first-entrant firm and the organizational form, and discounts protests against a specific firm but not those against the form (e.g., big-box stores). Further, the second entrant is likely to rely on the reaction of the first entrant as an indication of the meaning of the protest. Finally, all of these signaling effects will be stronger in markets in which the second entrant has no experience and so lacks local knowledge. The study provides broad support for our arguments.